Sliding ovary inside a hernia sac; a true emergency - Amin El Gohary (Elsevier, 2014)
We report two cases of female infants aged 5 and 6 months with strangulated twisted infracted ovaries inside hernial sacs requiring oophorectomy. Both presented with tender left sided groin swelling with skin erythema. One of presented a day prior to her scheduled admission and the other had her acute symptoms as her first presentation. This risk warrants treating the asymptomatic irreducible ovary as a true emergency.